Measurement of Nocturnal Scratching in Patients with Pruritus Using a Smartwatch: Initial Clinical Studies with the Itch Tracker App - Akihiko Ikoma; Toshiya Ebata; Laurent Chantalat; Kimitoshi Takemura; Fabienne Mizzi; Michel Poncet; Didier LeClercq (Medical Journals Sweden, 2018)
Three clinical studies were conducted to test a newly-developed app for smartwatches, which included an algorithm to measure nocturnal scratching using acceleration data. The first study in 5 patients with atopic dermatitis demonstrated high reliability of the app for measurement of scratching compared with video monitoring (positive predictive value 90.2 ± 6.6%, sensitivity 84.6 ± 10.2%, correlation of scratching duration per h r = 0.851-0.901, p<0.001). The second study in 20 patients with atopic dermatitis and 10 healthy volunteers showed that total scratching duration in patients was significantly longer than in healthy volunteers and correlated positively with Eczema Area and Severity Index (EASI) scores. In the third study, conducted in an open-entry manner in which 201 evaluable participants measured nocturnal scratching, those who self-reported itch or pruritic diseases had a significantly longer duration of scratching than those who did not. In conclusion, this app has a high reliability and potential clinical usefulness for measurement of nocturnal scratching.